Pengaruh Aplikasi Bakteri Endofit Terhadap Perkembangan Penyakit Darah (Ralstonia solanacearum Phylotipe IV) pada Tanaman Pisang - Husda Marwan; Rainiyati Rainiyati; Sri Mulyati (JURNAL BUDIDAYA PERTANIAN, 2020)
Endophytic bacterium EAL15 and EKK22 isolated from banana plants can suppress the development of blood diseases caused by Ralstonia solanacearum Phylotype IV in banana. This study aims to obtain the best liquid media for multiplying endophytic bacterial isolates EAL15 and EKK22, as well as the effect of the application of endophytic bacteria to the development of blood diseases in banana plants in the field. The liquid media tested were: coconut water waste + peptone, coconut water waste, and peptone. The application of endophytic bacterial suspension on Raja Bulu banana seedlings was done one month before planting, during planting, and 3 months after planting. Inoculum of R. solanacearum was inoculated on roots and banana flowers. Observations were made on the number of endophytic bacterial populations in each liquid media, the severity of blood diseases in plants and the incidence of blood diseases in bananas. The results showed that the liquid media of coconut water waste +peptone was the best medium for multiplying endophytic bacterial isolates. The application of endophytic bacteria influences the severity of blood diseases in banana plants and the incidence of diseases in bananas. The frequency of application of endophytic bacteria has no effect on the development of blood diseases in plants and bananas. Keywords: banana; blood disease; endophytic bacteria ABSTRAK Isolat bakteri endofit EAL15 dan EKK22 yang diisolasi dari tanaman pisang mampu menekan perkembangan penyakit darah yang disebabkan oleh Ralstonia solanacearum Phylotipe IV pada bibit pisang. Penelitian ini bertujuan untuk mendapatkan media cair terbaikuntuk memperbanyak isolat bakteri endofit EAL15 dan EKK22, serta pengaruh aplikasi bakteri endofit terhadap perkembangan penyakit darah pada tanaman pisang di lapangan. Media cair yang diuji yaitu : limbah air kelapa + pepton, limbah air kelapa, dan pepton. Aplikasi suspensi bakteri endofit pada bibit pisang Raja Bulu dilakukan satu bulan sebelum ditanam, saat tanam, dan 3 bulan setelah tanam. Inokulum R. solanacearumdiinokulasikan pada perakaran dan bunga pisang. Pengamatan dilakukan terhadap jumlah populasi bakteri endofit dalam masing-masing media cair, keparahan penyakit darah pada tanaman dan kejadian penyakit darah pada buah pisang. Hasil penelitian menunjukkan bahwa media limbah air kelapa + pepton merupakan media terbaik untuk memperbanyak isolat bakteri endofit. Aplikasi bakteri endofit berpengaruh terhadap keparahan penyakit darah pada tanaman pisang dan kejadian penyakit pada buah pisang. Frekuensi aplikasi bakteri endofit tidak berpengaruh terhadap perkembangan penyakit darah pada tanaman dan buah pisang. Kata kunci: Bakteri endofit, penyakit darah, pisang